1997
DOI: 10.1183/09031936.97.10051084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled versus intravenous vasodilators in experimental pulmonary hypertension

Abstract: Inhaled nitric oxide (NO) causes selective pulmonary vasodilation and improves gas exchange in acute lung failure. In experimental pulmonary hypertension, we compared the influence of the aerosolized vasodilatory prostaglandins (PG) PGI 2 and PGE 1 on vascular tone and gas exchange to that of infused prostanoids (PGI 2 , PGE 1 ) and inhaled NO.An increase of pulmonary artery pressure (Ppa) from 8 to ~34 mmHg was provoked by continuous infusion of U-46619 (thromboxane A 2 (TxA 2 ) analogue) in blood-free perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 40 publications
2
49
0
5
Order By: Relevance
“…In an in vitro study, we have demonstrated that the emitted dose of IPGE 1 following jet nebulization in a neonatal ventilator circuit was 32-40% (26). In the present study, we used a high dose of IPGE 1 , 1200 ng/kg/min, corresponding to a total dose of ~3,500 μg of PGE 1 administered over 24 h. Compared to doses known to reduce pulmonary hypertension in patients (8-300 ng/kg/min), this represents a high dose (7)(8)(9)20,28,36). A dose of 1200 ng/ kg/min was chosen as this represents a dose four times the maximal dose that has been reported in humans and when given over a 24-hour period represents the cumulative dose that would be delivered over several days in the clinically used doses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an in vitro study, we have demonstrated that the emitted dose of IPGE 1 following jet nebulization in a neonatal ventilator circuit was 32-40% (26). In the present study, we used a high dose of IPGE 1 , 1200 ng/kg/min, corresponding to a total dose of ~3,500 μg of PGE 1 administered over 24 h. Compared to doses known to reduce pulmonary hypertension in patients (8-300 ng/kg/min), this represents a high dose (7)(8)(9)20,28,36). A dose of 1200 ng/ kg/min was chosen as this represents a dose four times the maximal dose that has been reported in humans and when given over a 24-hour period represents the cumulative dose that would be delivered over several days in the clinically used doses.…”
Section: Discussionmentioning
confidence: 91%
“…Intravenous PGE 1 (ivPGE 1 ) and PGI 2 , potent vasodilators used empirically in the treatment of NHRF, are associated with systemic hypotension and worsening of oxygenation due to increased venous admixture (2)(3)(4)(5)(6). This has led investigators to explore the delivery of PGE 1 and PGI 2 directly to the lungs as an inhalation, thus minimizing systemic effects and achieving selective pulmonary vasodilation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Compared to PGI 2 , PGE 1 has a shorter half-life, lower pH (6.3 versus 10.5), bronchodilator action, anti-proliferative and anti-inflammatory effects on the alveolar, interstitial and vascular spaces of the lung (8,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…(22) Experimental studies have shown that the vasodilator properties of IPGI 2 are as effective as are those of nitric oxide. (23) The use of inhaled PGI 2 is with changes in vascular permeability due to an immune phenomenon related to allergy to dextran. (30) Because dextran is a compound that is found in the low potassium (Perfadex ® ) solution used in lung preservation, there will always be a possibility that that factor contributes to pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to a blood-free perfusion, ET-1 effects on peripheral blood cells can be neglected. Since some superiority of aerosolized vasoactive substances has been shown before (14,28), we have chosen this route of application into the target organ to maximize benefit/risk ratio of the substances. We aimed to establish an ET-1-induced PH without lung edema formation, giving us the chance to describe the "pure" vascular action of ET-1 in the pulmonary circulation.…”
Section: Discussionmentioning
confidence: 99%